DYNAMIC STRATEGIC-FIT DAN KINERJA: STUDI PADA PERBANKAN SYARIAH - Laela, Sugiyarti F. (UI Scholars Hub, 2014)
Although the growth of Islamic banking assets is still high, the market share of Islamic banking reached only ± 4,92% by the end of May 2014. Islamic banks should implement an appropriate strategy to face dynamic changes in the business environment. The education strategy is one of the business strategies of Islamic banks that remain a priority today. It provides information and understanding for society about the function, role, activities, and products as well as services of Islamic banks. This study examines the impact of fit between the education strategy and contingency variables (known as strategic-fit) on performance. The contingency variables include efficiency of input, organizational competency, CEO tenure, and composition of shariah supervisory board. The performance of Islamic banks consists of both financial and social performances. Using the data from 1997 to 2012 of 10 fully-fledge Islamic banks in Indonesia and least squares method, this study shows that the efficiency of input has a positive effect on the educational strategy implementation. On the other hand, the composition of shariah supervisory board and organizational competency negatively affect the implementation of the educational strategy. Nevertheless, there is no strong evidence that CEO tenure influences the implementation of the educational strategy. Adopting the method of Van de Ven and Drazin (1985) to determine the degree of strategic misfit, this study finds that the misfit between educational strategy and its contingency variables has a negative effect on financial performance, but no significant effect of misfit on social performance.